Analisis Pengaruh Sistem Pelayanan Self Service dan Store Atmosphere Terhadap Kepuasan Pelanggan pada Dali Coffee Shop Karawang - Sofyan Iswanto; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Coffee shops, as retail establishments that specialize in offering various types of coffee and related beverages, play an important role in meeting consumers' growing needs for a unique and quality coffee experience. This study aims to analyze the effect of self-service service system and store atmosphere on customer satisfaction at Dali Coffee Shop in Karawang. This research uses quantitative methods by distributing questionnaires to customers who visit the store. This study uses a sampling technique that uses non-probability sampling techniques with a purposive sampling approach, namely purposive sampling by determining the number of respondents as many as 100 respondents. The results of this study indicate that the self service system and store atmosphere have a positive and significant effect on customer satisfaction. The conclusion in this study is that the variables of self service system and store atmosphere have a good influence simultaneously on customer satisfaction at Dali Coffee Shop.